Alguém ajuda a responder! pfv! obg!
Anexos:
![](https://pt-static.z-dn.net/files/d03/e3c0d186edbbd3a5c2e08a5fe428ebfd.jpg)
Soluções para a tarefa
Respondido por
1
[√x+ √(x-1)]²= √(2x-3)²
x+ (x-1) + 2·√x · √(x-1) = 2x-3
2·√x · √(x-1) = 2x-3-x-x+1
2·√x · √(x-1) = -2
√x · √(x-1) = -1
x·(x-1)=1
x²-x-1=0 com x>3/2
==> x= (1+√5)/2 = phi somente se fosse √x - √(x-1)= √(2x-3)
theo82:
obg!
Perguntas interessantes
Matemática,
8 meses atrás
Biologia,
8 meses atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Contabilidade,
1 ano atrás